Mortality and Hospitalizations in Mexican Patients with Inflammatory Bowel Disease: Results from a Nationwide Health Registry - Andrea Sarmiento-Aguilar; María J. Ríos-Blancas; Jesús K. Yamamoto-Furusho (Canadian Journal of Gastroenterology and Hepatology)
Background. Incidence of inflammatory bowel disease (IBD), which includes ulcerative colitis (UC) and Crohn’s disease (CD), is increasing worldwide; nevertheless, it is still unknown if this is the case in Mexico. Thus, the aim of this study was to analyze the distribution and trends of hospital discharges (HD) (for the period between 2004 and 2015) and deaths (for the period between 2004 and 2013) reported for UC and CD in Mexico. Methods. Quantitative cross-sectional study was performed. Secondary data sources analysis was performed through Dynamic Cubes of the General Direction of Health Information; variables were categorized by diagnosis, age, sex, and state. The Mann–Whitney U test was used to analyze the differences between the first and last years that were studied. Statistical analysis was performed in SPSS v.24. Results. The number of HD increased by 98.9% between 2004 and 2015 (IBD: p=0.033, CD: p=0.009, UC: p=0.051); it was more frequent, for both sexes and diagnoses, between 15 and 44 years, with a second peak for men with UC (between 45 and 64 years). Deaths increased by 96.2% from 2004 to 2011 (IBD: p=0.056, CD: p=0.064, UC: p=0.04). UC is three times more frequent than CD. Mexico City has the highest number of HD (4,179; 22.7%) while the state of Veracruz has the highest number of deaths (273; 38.2%). Conclusions. HD for IBD in Mexico is increasing significantly; the number of deaths increased until 2011, but from then on, they are apparently decreasing. IBD affects Mexican people without any gender predominance, often affecting patients between 15 and 44 years of age. UC is three times more frequent than CD.